Midwifery Education Institutions in Italy Creation and Validation of Clinical Preceptors' Assessment Tool: Students' and Expert Midwives' Views - Paola Agnese Mauri; Ivan Cortinovis; Norma Nilde Guerrini Contini; Marta Soldi (MDPI AG, 2020)
Background: The aim of the study is to create and validate a midwifery preceptor's evaluation form to be used by midwifery students. The International Confederation of Midwives recommends that clinical placements need to be supervised by a preceptor in order to be efficient for students who, in this way, gain competence and proper practice within the midwifery practical area. Methods: This is an observational multi-center transversal study and leads to the validation of an evaluation questionnaire. Methodically, the following steps were followed: literature review, focus group with midwifery students, meeting between expert midwives, creation of the preceptor's assessment form, filling in of the forms by midwifery students and expert midwives, and validation of the form. The study was carried out in eight Italian universities and included eighty-eight midwifery students and eight midwives. Results and Conclusion: A midwifery preceptor's assessment questionnaire was created made up of four attribute areas which, as a total, included 33 items. Cronbach's alpha score was calculated after examining the forms filled in by students and expert midwives. An alpha score of 0.97-0.85 was obtained. The result was Pearson Correlation Coefficient r = 0.78.